Effect of percutaneous electrical stimulation with high-frequency alternating currents at 30 kHz on the sensory-motor system - Álvarez, David Martín-Caro; Serrano-Muñoz, Diego; Fernández-Pérez, Juan José; Gómez-Soriano, Julio; Avendaño-Coy, Juan (Frontiers in Neuroscience, 2023)
Background: unmodulated high-frequency alternating currents (HFAC) are employed for producing peripheral nerves block. HFAC have been applied in humans with frequencies up to 20 kHz, whether transcutaneously, percutaneously, or via surgically-implanted electrodes. The aim of this study was to assess the effect of percutaneous HFAC, applied with ultrasound-guided needles at 30 kHz, on the sensory-motor nerve conduction of healthy volunteers. Methods: a parallel, double-blind, randomized clinical trial with a placebo control was conducted. Percutaneous HFAC at 30 kHz or sham stimulation was applied via ultrasound-guided needles in 48 healthy volunteers (n=24 in each group) for 20 minutes. The assessed outcome variables were pressure pain threshold (PPT), mechanical detection threshold (MDT), maximal finger flexion strength (MFFS), antidromic sensory nerve action potential (SNAP), hand temperature, and subjective sensations by the participants. The measurements were recorded pre-intervention, during the stimulation (at 15 min), immediately post-intervention (at 20 min), and 15 min after the end of treatment. Results: the PPT increased in the active group compared with sham stimulation, both during the intervention [14.7%; 95% confidence interval (CI): 4.4–25.0], immediately post-intervention (16.9%; 95%CI: -7.2–26.5), and 15 min after the end of the stimulation (14.3%; 95%CI: 4.4–24.3) (p<0.01). The proportion of participants who reported feelings of numbness and heaviness was significantly higher in the active group (46% and 50%, respectively) than in the sham group (8% and 18%, respectively) (p<0.05). No intergroup differences were observed in the remaining outcome variables. No unexpected adverse effects derived from the electrical stimulation were reported. Conclusions: percutaneous stimulation with HFAC at 30 kHz applied to the median nerve increased the PPT and subjective perception of numbness and heaviness. Future research should evaluate its potential therapeutic effect in people with pain.